Layered modeling and generation of Pollock’s drip style - Zheng, Yan; Nie, Xuecheng; Meng, Zhaopeng; Feng, Wei; Zhang, Kang (The Visual computer, 2015)
In this paper, we propose a layered approach to model Jackson Pollock’s dripping style of paintings. Having analyzed fractal-based algorithms and observed the details of Pollock’s paintings, we designed a layered modeling approach that divides Pollock’s artwork into four layers: from bottom up are background layer, irregular shape layer, line layer and water drop layer. The layers are drawn sequentially and independent, forming the desired Pollock style. We have developed a program using Processing to generate artworks of the dripping style. The parameters of our program can be randomly generated or tuned by the user, supporting high flexibility and effectiveness. Experimental results show that our layered modeling approach can systematically generate images resembling Pollock’s dripping style.